Identification and Distribution of Wild Toxic Inocybe spp., and Edible Tricholoma Mushrooms in Jordan - Al-Momany, Ahmad Mohamad (Jordan Journal of Agricultural Sciences, 2025)
A survey and collection of wild mushroom samples from Jordan was done for two consecutive years. Woodlands, grasslands as well as lawns and gardens were included in the study. All mushroom samples were classified according to morphological characteristics of the cap, stipe, gills, attachment of the cap to the stipe, and spore dimensions. Nine Inocybe species as I. atripes. I. cincinnata, I. cookie, I. corydaline, I. flocculosa, I. geophylla, I. hirtella, I. lacera, and I. rimosoides were found in north and middle Jordan and all of them were poisonous. While seven Tricholoma species T. myomyces, T. portentosum, T. sejunctum, T. terreum, T. pardinum, T. venenatum, and T. virgatum were found in different locations in Jordan one of them was poisonous which was Tricholoma pardinum and the other one Tricholoma myomyces was not edible. Seven Inocybe spp. and two Tricholoma spp. were reported for the first time as new records from Jordan. The most important mushroom that was found everywhere in Jordan was Tricholoma terreum. These wild nutritious mushrooms play an important role in the ecosystem and food security. This study shows the wide biodiversity of wild mushrooms in Jordan.